Analisis Kualitas Pembelajaran Daring di Sekolah Tinggi Teknologi Cipasung - Ernawati; Maudy Sriwahyuni Yusuf (LPPM Sekolah Tinggi Teknologi Cipasung, 2023)
Sekolah Tinggi Teknologi Cipasung (STT Cipasung) is one of the formal higher education institutions in the Cipasung Islamic Boarding School, Singaparna, Tasikmalaya, West Java. During the COVID-19 pandemic, all academic and non-academic activities at the Sekolah Tinggi Teknologi Cipasung were changed to Work From Home (WFH). Learning carried out online certainly has many problems that arise due to factors such as gadgets, quotas, networks, concentration, and environment causing an increase in students who do not pass courses and a decrease in student IP scores. For this reason, the Cipasung College of Technology needs to conduct research on the analysis of the quality of online learning. This research uses Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. The results of data processing that the 18 attributes measured resulted in a negative gap value, this indicates that it has not met student expectations. Based on the results of the IPA kertesius diagram, the attributes of online learning that need to be improved are the consistency of the lecturers giving lectures well and the lecturers being reliable in managing the class during online learning.